Звезда не активнаЗвезда не активнаЗвезда не активнаЗвезда не активнаЗвезда не активна
\begin{equation} 1) \log_{2}(-x)+\log_{2}(1-x) \leq 1; \end{equation} \begin{equation} \log_{2}(-x(1-x)) \leq \log_{2}2; \end{equation} \begin{equation} \left\{\begin{matrix} -x(1-x) \leq 2, & \\ -x < 0, & \\ 1-x > 0; & \end{matrix}\right. \left\{\begin{matrix} -x+x^{2}-2 \leq 0, & \\ x < 0, & \\ x < 1; & \end{matrix}\right. \end{equation} \begin{equation} \left\{\begin{matrix} x^{2}-x-2 \leq 0, & \\ x < 0; & \end{matrix}\right. \left\{\begin{matrix} -1 \leq x \leq 2, & \\ x < 0; & \end{matrix}\right. -1 \leq x < 0. \end{equation} Відповідь:[-1;0). \begin{equation} 2) \log_{0,2}(x-1)+\log_{0,2}(x+3) \geq -1; \end{equation} \begin{equation} \log_{0,2}((x+3)(x-1)) \geq \log_{0,2}5; \end{equation} \begin{equation} \left\{\begin{matrix} (x-1)(x+3) \leq 5, & \\ x-1 > 0, & \\ x+3 > 0; & \end{matrix}\right. \left\{\begin{matrix} x^{2}+3x-x-3-5 \leq 0, & \\ x > 1, & \\ x > -3; & \end{matrix}\right. \end{equation} \begin{equation} \left\{\begin{matrix} x^{2}+2x-8 \leq 0, & \\ x > 1; & \end{matrix}\right. \left\{\begin{matrix} -4 \leq x \leq 2, & \\ x > 1; & \end{matrix}\right. 1 < x \leq 2. \end{equation} Відповідь:(1;2]. \begin{equation} 3)\log_{3}(x-2)+\log_{3}(x-10) \leq 2; \end{equation} \begin{equation} \log_{3}(x-2)(x-10) \leq \log_{3}9; \end{equation} \begin{equation} \left\{\begin{matrix} (x-2)(x-10)-9 \geq 0, & \\ x-2 > 0, & \\ x-10 > 0; & \end{matrix}\right. \end{equation} \begin{equation} \left\{\begin{matrix} x^{2}-10x-2x+20-9 \geq 0, & \\ x > 2, & \\ x > 10; & \end{matrix}\right. \end{equation} \begin{equation} \left\{\begin{matrix} x^{2}-12x+11 \geq 0, & \\ x > 10; & \end{matrix}\right. \left\{\begin{matrix} [x \leq 1, & \\ [x \geq 11, & \\ x > 10; & \end{matrix}\right. x \geq 11. \end{equation} Відповідь: \begin{equation} [11; + \infty) \end{equation} \begin{equation} 4) \log_{7}x+\log_{7}(3x-8) \geq 1+2 \log_{7}2; \end{equation} \begin{equation} \log_{7}(x(3x-8)) \geq \log_{7}(7*2^{2}); \end{equation} \begin{equation} \log_{7}(3x^{2}-8x) \geq \log_{7}28; \left\{\begin{matrix} 3x^{2}-8x \geq 28, & \\ x > 0, & \\ 3x-8 > 0; & \end{matrix}\right. \end{equation} \begin{equation} \left\{\begin{matrix} 3x^{2}-8x-28 \geq 0, & \\ x > 0, & \\ x > \frac{8}{3}; & \end{matrix}\right. \left\{\begin{matrix} [x \leq -2, & \\ [x \geq \frac{14}{3}, & \\ x > \frac{8}{3}; & \end{matrix}\right. x \geq \frac{14}{3}. \end{equation} Відповідь: \begin{equation} [\frac{14}{3}; + \infty). \end{equation}
Звезда не активнаЗвезда не активнаЗвезда не активнаЗвезда не активнаЗвезда не активна
\begin{equation} 1)\lg x+\lg (x-3) > 1; \lg(x(x-3)) > \lg 10; \end{equation} \begin{equation} \left\{\begin{matrix} x(x-3) > 10, & \\ x-3 > 0, & \\ x > 0; & \end{matrix}\right. \left\{\begin{matrix} x^{2}-3x-10 > 0, & \\ x > 3; & \end{matrix}\right. \end{equation} \begin{equation} \left\{\begin{matrix} [x , -2, & \\ [x > 5, & \\ x > 3; & \end{matrix}\right. x > 5. \end{equation} Відповідь: \begin{equation} (5;+\infty ) \end{equation} \begin{equation} 2) \log_{\frac{1}{2}}(x+2)+ \log_{\frac{1}{3}} x < -1; \end{equation} \begin{equation} \log_{\frac{1}{3}}((x+2)*x) < \log_{\frac{1}{3}}3 \end{equation} \begin{equation} \left\{\begin{matrix} x(x+2) > 3, & \\ x > 0, & \\ x+2 > 0; & \end{matrix}\right. \left\{\begin{matrix} x^{2}+2x-3 > 0, & \\ x > 0, & \\ x > -2; & \end{matrix}\right. \end{equation} \begin{equation} \left\{\begin{matrix} [x < -3, & \\ [x > 1, & \\ x > 0; & \end{matrix}\right. x > 1. \end{equation} Відповідь: \begin{equation} (1;+ \infty) \end{equation} \begin{equation} 3) \log_{2}x+\log_{2}(x+4) < 5; \log_{2}(x(x+4)) < \log_{2}32; \end{equation} \begin{equation} \left\{\begin{matrix} x^{2}+4x < 32, & \\ x > 0, & \\ x+4 > 0; & \end{matrix}\right. \left\{\begin{matrix} x^{2}+4x-32 < 0, & \\ x > 0; & \end{matrix}\right. \end{equation} \begin{equation} \left\{\begin{matrix} -8 < x < 4, & \\ x > 0; & \end{matrix}\right. 0 < x < 4. \end{equation} Відповідь:(0;4). \begin{equation} 4) \log_{0,1}(x-5)+ \log_{0,1}(x-2) \geq -1; \end{equation} \begin{equation} \log_{0,1}((x-5)(x-2)) \geq \log_{0,1}10; \end{equation} \begin{equation} \left\{\begin{matrix} (x-5)(x-2) \leq 10, & \\ x-5 > 0, & \\ x-2 > 0; & \end{matrix}\right. \left\{\begin{matrix} x^{2}-2x-5x+10 \leq 10, & \\ x > 5, & \\ x > 2; & \end{matrix}\right. \end{equation} \begin{equation} \left\{\begin{matrix} x(x-7) \leq 0, & \\ x > 5; & \end{matrix}\right. \left\{\begin{matrix} 0 \leq x \leq 7, & \\ x > 5; & \end{matrix}\right. 5 < x \leq 7. \end{equation} Відповідь: (5;7]. \begin{equation} 5) \log_{6}(5x+8)+\log_{6}(x+1) \leq 1- \log_{6}3; \end{equation} \begin{equation} \log_{6}(5x+8)+\log_{6}(x+1) \leq \log_{6}6 - \log_{6}3; \end{equation} \begin{equation} \log_{6}(5x+8)(x+1) \leq \log_{6}\frac{6}{3}; \end{equation} \begin{equation} \left\{\begin{matrix} (5x+8)(x+1) \leq 2, & \\ 5x+8 > 0, & \\ x+1 > 0; & \end{matrix}\right. \end{equation} \begin{equation} \left\{\begin{matrix} 5x^{2}+5x+8x+8-2 \leq 0, & \\ x > -\frac{8}{5}, & \\ x > - 1; & \end{matrix}\right. \left\{\begin{matrix} 5x^{2}+13x+6 \leq 0, & \\ x > -1; & \end{matrix}\right. \end{equation} \begin{equation} \left\{\begin{matrix} -2 \leq x \leq -\frac{3}{5}, & \\ x > -1; & \end{matrix}\right. -1 < x \leq -\frac{3}{5}. \end{equation} Відповідь: \begin{equation} (-1; -\frac{3}{5}]. \end{equation} \begin{equation} 6) \log_{3}(1-x)+\log_{3}(-5x-2) \geq 2 \log_{3}2+1; \end{equation} \begin{equation} \log_{3}((1-x)(-5x-2)) \leq \log_{3}(4*3); \end{equation} \begin{equation} \left\{\begin{matrix} (1-x)(-5x-2) \leq 12, & \\ 1-x > 0, & \\ -5x-2 > 0; & \end{matrix}\right. \end{equation} \begin{equation} \left\{\begin{matrix} -5x-2+5x^{2}+2x-12 \leq 0, & \\ x < 1, & \\ x < - \frac{2}{5}; & \end{matrix}\right. \end{equation} \begin{equation} \left\{\begin{matrix} 5x^{2}-3x-14 \geq 0, & \\ x < -0,4; & \end{matrix}\right. \left\{\begin{matrix} [x < -1,4, & \\ [x > 2, & \\ x < -0,4; & \end{matrix}\right. x < -1,4. \end{equation} Відповідь: \begin{equation} (- \infty; -1,4]. \end{equation}
Звезда не активнаЗвезда не активнаЗвезда не активнаЗвезда не активнаЗвезда не активна
\begin{equation} 1)f(0)=e^{-2.0}=e^{0}=1; \end{equation} \begin{equation} {f}'(x)=e^{-2x}*(-2)=-2e^{-2x}; \end{equation} \begin{equation} {f}'(0)=-2e^{-3.0}=-2; \end{equation} \begin{equation} y=1+(-2)(x-0);y=1-2x; \end{equation} \begin{equation} 2)f(0)=e^{0}+ \sin 0=1+0=1; \end{equation} \begin{equation} {f}'(x)=e^{x}+ \cos x; \end{equation} \begin{equation} {f}'(0)=e^{0}+ \cos 0=1+1=2; \end{equation} \begin{equation} y=1+2(x-0);y=2x+1; \end{equation} \begin{equation} 3)f(1)=1*2=2; \end{equation} \begin{equation} {f}'(x)=2^{x}+x*2^{x} \ln 2=2^{x}(1+ \ln 2*x); \end{equation} \begin{equation} {f}'(1)=2(1+ \ln 2*1)=2+2 \ln 2; \end{equation} \begin{equation} y=2+(2+2 \ln 2)(x-1); \end{equation} \begin{equation} y=2+2x-2+2x \ln 2-2 \ln 2; \end{equation} \begin{equation} y=2x(1- \ln 2)-2 \ln 2; \end{equation} \begin{equation} f(1)=3*1+ \ln 1=3+0=3; \end{equation} \begin{equation} {f}'(x)=3+\frac{1}{x}; {f}'(1)=3+\frac{1}{1}=4; \end{equation} \begin{equation} y=3+4(x-1);y=4x-1; \end{equation}
Звезда не активнаЗвезда не активнаЗвезда не активнаЗвезда не активнаЗвезда не активна
\begin{equation} 2)f(x)=\frac{1}{2}x^{2}- \ln x^{2},x_{0}=4; \end{equation} \begin{equation} {f}'(x)=\frac{1}{2}*2x-\frac{1}{x^{2}}*2x=2-\frac{2}{x}; \end{equation} \begin{equation} {f}'(4)=4-\frac{2}{4}=3\frac{2}{4}=3,5; \end{equation}